Developing Pictionary Game Media to Teach Speaking and Writing Skills for VII F Grade at MTsN 3 Blitar - Anfa, Yunika Lailati; Rofi'ah, Siti; Saifudin, Ahmad; Makrifah, Istina Atul (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
The purpose of this project is to create an educational media in the form of a Pictionary Game to help seventh-grade students at MTsN 3 Blitar improve their speaking and writing abilities. Many students considered English difficult and uninteresting owing to traditional teaching techniques, which resulted in poor enthusiasm and confidence in utilizing the language. The researcher created and assessed the efficacy of Pictionary Game media using the ADDIE paradigm. Data gathering methods included observations, questionnaires, and pre- and post-tests. Media, instrument, and material specialists validated the product and gave it "very valid" ratings ranging from 80% to 92.5%. The post-test findings showed a 10.69% improvement in speaking and a 12.7% improvement in writing abilities over the pre-test levels. Student satisfaction reached 85%, indicating the media was “very feasible” for learning. These findings suggest that Pictionary Game media can effectively improve English speaking and writing skills in a fun and engaging way.